Hubungan Penggunaan KB Suntik 3 Bulan Dengan Kenaikan Berat Badan Pada Wanita Akseptor KB - Citra M, Resi; Handayani, Welly (JUKEJ : Jurnal Kesehatan Jompa, 2024)
Three-month injectable contraception is one of the hormonal family planning methods commonly used by women in Indonesia. One of the frequently reported side effects of the 3-month injectable contraceptive is weight gain. This is caused by the effect of the progestin hormone contained in the injection, which can influence metabolism and hormonal balance in the body. This study aims to determine the relationship between the use of the 3-month injectable contraceptive and weight gain in female contraceptive acceptors at the Naras Health Center in 2024. The research employs an analytical observational method with a cross-sectional approach. The sample includes women who are acceptors of the 3-month injectable contraceptive registered at the Naras Health Center in 2024. Data was collected through interviews, weight measurements before and after the use of the injectable contraceptive over a specific period, and medical records. Data analysis was carried out using Pearson's correlation test to examine the relationship between the use of the 3-month injectable contraceptive and weight gain. The results of the study indicate that most women who use the 3-month injectable contraceptive experience weight gain within the first six months of use. There is a significant relationship between the use of the 3-month injectable contraceptive and weight gain (p < 0.05), with p=0.002, where the average weight gain is 2-5 kg after six months of use. The use of the 3-month injectable contraceptive is associated with weight gain in female contraceptive acceptors at the Naras Health Center in 2024. Therefore, it is necessary to educate contraceptive acceptors about this potential side effect and encourage preventive measures through a healthy diet and regular physical activity